Dinamika Penangkapan Ikan Motan (Thynnichthys thynnoides, Bleeker 1852) dan Bulan Bulan (Helostoma temminckii, Cuvier 1829) di Perairan Sungai Kampar, Kota Pekanbaru, Riau - Az Zahra, Aisyah Sarrah; Wulandari, Yunia Afrioni; Rais, Aroef (Seminar Nasional Lahan Suboptimal, 2024)
Azzahra, A. S., Wulandari, Y. A., & Rais, A. (2024). The dynamic fishing of motan (Thynnichthys thynnoides, Bleeker 1852) and bulan- bulan (Helostoma temminckii, Cuvier 1829) in The Kampar River, Pekanbaru City, Riau. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-12 Tahun 2024, Palembangg 21 Oktober 2024. (pp. 563–572). Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Motan fish (Thynnichthys thynnoides) and Bulan-bulan (Helostoma temminckii) are fish that have economic value as food fish for the people of Pekanbaru City, Riau. This fish is often caught in canals, oxbows, swamps in the waters of the Kampar River, and one of them is located in the swamps and lakes of Buluh Cina Village. The aim of this research was to evaluate the mortality rate and level of exploitation of the moltan and lunar fish populations in the waters of the Kampar River. This research was carried out from April to October 2021. The research method used an observation method where samples were obtained from fishermen's catches whose length values were measured every month. Data analysis was carried out with the help of FiSAT II software. The results of analysis using FiSAT II showed that for motan fish the total mortality value (Z) = 1.41; natural mortality (M) = 1.1; fishing mortality (F) = 0.31; and exploitation rate (E) = 0.22. In lunar fish the total mortality value (Z) = 3.33; natural mortality (M) = 1.12; fishing mortality (F) = 2.21; and exploitation rate (E) = 0.66. The exploitation level value shows that lunar fishing has experienced overfishing (E>0.5), while exploitation of motan fish can still be increased (E<0.5).